460 Remote Orthopaedic Clinics during COVID-19: Lessons for a Sustainable Future. (12th October 2021) - Curtis, A; Parwaiz, H; Winkworth, C; Sweeting, L; Pallant, L; Davoudi, K; Smith, E; Chin, K; Kelsey, M; Brankin-Frisby, T; Stevenson, A
Abstract: Aim: The COVID-19 pandemic has led to a focus on non-face to face (NF2F) orthopaedic clinics. Our aim was to establish whether NF2F clinics were sustainable according to the 'Triple Bottom Line' framework by taking account of the impact on patients, the planet and financial cost. Method: This retrospective cohort study was carried out at a large DGH with 261 patients identified as having undergone F2F or NF2F orthopaedic consultations (April 2020). These patients were contacted by telephone to establish their experience, mode of transport and preference for future consultations. Data was also collected relating to environmental and financial costs to the patient and trust. Results: Final analysis included 180 patients (69%): 42% had a F2F consultation and 58% a NF2F consultation. There was no significant difference between each group in terms of convenience, ease of communication, subjective patient safety, or overall satisfaction rating ( p >0.05). 80% of NF2F patients would be happy with virtual consultations in future. Mean journey distance was 18.6 miles leading to a reduction in total carbon emissions of 563.9kg CO2 e (66%), equating to 2106 miles in a medium sized car. The hospital visit carbon cost (heating, lighting, and waste generation) was reduced by 3, 967kg CO2 e (58%). The financial cost (petrol and parking) was also reduced by an average of £8.96 per person. Conclusions: NF2F consultations are aligned to the NHS 'Long Term Plan'. They (i) deliver high patient satisfaction with equivalent outcomes to F2F consultations; (ii) have reduced carbon emissions from transportation and hospital running; and (iii) are cheaper.